Nonequilibrium thermodynamics modeling of the rheological response of cement pastes - Ioannou, Amalia K.; Stephanou, Pavlos S. (My University, 2023)
Undoubtedly, cement is one of the most important materials in the construction industry. For its effective use, it is particularly important to fully comprehend the rheological behavior of cement paste. When cement is mixed with water, a suspension is initially formed and the rate of hydrolysis reactions accelerates leading to the formation of a new irreversible structure, i.e., the cement paste gradually solidifies. At the same time, the viscosity of the paste initially decreases with time, while at long times it gradually increases due to the formation of the irreversible structure. We herein introduce a continuum model for predicting the rheological behavior of cement pastes. The model is developed using nonequilibrium thermodynamics, in particular, the Generalized Brackets formalism, to guarantee model admissibility with thermodynamic laws. To this end, we consider two scalar structural variables: a reversible, λ rev , characterizing the reversible structure, and an irreversible one, λ irr , characterizing the irreversible structure resulting from the hydrolysis reactions. Also, we consider a tensorial structural variable, the conformation tensor c , to characterize the deformation of the cement particles. The predictions of the new model compare reasonably well with available experimental data, especially at large times, and further highlight the capacity of the new model to address the thixotropic behavior of cement pastes. It is expected that the use of this model in concrete rheology simulators will allow for the in silico testing and tailor-designing of concrete to meet specific processing needs.
Keywords: Viscoplastic material; Hamiltonian mechanics; Mechanical stress; Nonequilibrium thermodynamics; Cement; Flocculation; Rheology and fluid dynamics; Rheological properties; Shear thinning; Viscosity